2021
DOI: 10.3390/ijms221910362
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Experience Induces the Expression of Gastrin-Releasing Peptide and Oxytocin Receptors in the Spinal Ejaculation Generator in Rats

Abstract: Male sexual function in mammals is controlled by the brain neural circuits and the spinal cord centers located in the lamina X of the lumbar spinal cord (L3–L4). Recently, we reported that hypothalamic oxytocin neurons project to the lumbar spinal cord to activate the neurons located in the dorsal lamina X of the lumbar spinal cord (dXL) via oxytocin receptors, thereby facilitating male sexual activity. Sexual experiences can influence male sexual activity in rats. However, how this experience affects the brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In contrast, the mushroom spine density in the mPOA decreases and the expression of vgf, which encodes the neuropeptide precursor VGF in the mPOA, affects behavior (shortening mating latency) following mating and ejaculation experience in male rats 5 , 11 . We recently reported that the expression of gastrin-releasing peptide and oxytocin receptors is increased in the spinal ejaculation generator in the lumbosacral cord after the first mating experience with ejaculation in male rats 12 . Furthermore, the first mating experience also decreases neuronal activity in the center part of the mPOA, suggesting that the first mating experience reconstructs the neural network associated with male mating behavior 13 .…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, the mushroom spine density in the mPOA decreases and the expression of vgf, which encodes the neuropeptide precursor VGF in the mPOA, affects behavior (shortening mating latency) following mating and ejaculation experience in male rats 5 , 11 . We recently reported that the expression of gastrin-releasing peptide and oxytocin receptors is increased in the spinal ejaculation generator in the lumbosacral cord after the first mating experience with ejaculation in male rats 12 . Furthermore, the first mating experience also decreases neuronal activity in the center part of the mPOA, suggesting that the first mating experience reconstructs the neural network associated with male mating behavior 13 .…”
Section: Introductionmentioning
confidence: 98%